Design patterns for embedded systems in C : an embedded software engineering toolkit - Douglass, Bruce Powel (Amsterdam : Newnes, 2011)
A recent survey stated that 52% of embedded projects are late by 4-5 months. This book can help get those projects in on-time with design patterns. The author carefully takes into account the special concerns found in designing and developing embedded applications specifically concurrency, communication, speed, and memory usage. Patterns are given in UML (Unified Modeling Language) with examples including ANSI C for direct and practical application to C code.
Chapter 1. What is embedded programming? -- Chapter 2. Embedded programming with the harmony for embedded real-time process -- Chapter 3. Design patterns for accessing hardware -- Chapter 4. Design patters for embedding concurrency and resource management -- Chapter 5. Design patters for state machines -- Chapter 6. Safety and reliability patters -- Appendix -- Index.
Includes index.
Keywords: C (COMPUTER PROGRAM LANGUAGE)